IDENTIFIKASI PENYEBAB KEGAGALAN DAN APLIKASI FIBER REINFORCED COMPOSITE PADA SPLINTING - Putri Ovieza Maizar; Kosno Suprianto (Andalas Dental Journal, 2018)
Periodontal disease is a disease characterized by inflammation of the gingiva, loss of attachment, and damage to the alveolar bone. Bone loss caused by periodontitis may lead to tooth mobility which causes discomfort during mastication, difficulty in maintaining oral hygiene, and persistent inflammation which results in tooth loss. Splinting is a treatment to stabilize a tooth that is experiencing mobility due to periodontal problems. The most common alternative is the use of a fiber reinforced composite material that bonds to the tooth surface. Fiber works functionally, has good aesthetics, and can improve tooth stability due to mobility that occurs due to bone loss. However, in practice fiber splint also has the potential to fail due to several micro mechanisms. One of them was found in this case report. The following case report is regarding the use of a fiber reinforced composite splinting on lower anterior teeth involving two posterior teeth.